Two distinct thyroid tumours in a patient with Cowden syndrome carrying both a 10q23 and a mitochondrial DNA germline deletion. Issue 11 (16th September 2011) - Pradella, Laura Maria; Zuntini, Roberta; Magini, Pamela; Ceccarelli, Claudio; Neri, Iria; Cerasoli, Serenella; Graziano, Claudio; Gasparre, Giuseppe; Turchetti, Daniela
Abstract : Background: Cowden syndrome (CS) is an autosomal dominant disorder characterised by macrocephaly, specific mucocutaneous features and predisposition to benign and malignant tumours. Detectable mutations in the PTEN gene account for 80–85% of cases. Methods/Results: Here, the authors report a patient with macrocephaly and typical CS mucocutaneous features who developed dysplastic cerebellar gangliocytoma and two synchronous thyroid cancers of papillary and oncocytic type, in whom a germline 500-Kb deletion on chromosome 10q23 including PTEN was detected. Molecular characterisation of thyroid cancer led to the identification of the oncogenic BRAFV600E mutation in the papillary carcinoma. BRAFV600E has been proposed to cause cancer only in the presence of a tumour-suppressor mutation, which, in this case, could be the PTEN deletion. In the oncocytic carcinoma, a large deletion in the mitochondrial-DNA-encoded MTND1 was found, associated with respiratory complex I disassembly, which was subsequently shown to be a constitutional, de novo genetic lesion. Conclusions: This is the first reported case of a patient with CS carrying constitutional deletions in both the nuclear and the mitochondrial genome that might help elucidate some aspects of CS pathogenesis.